Clinical Outcome of Antiviral Therapy on COVID-19 Patients - Aliska, Gestina; Putra, Andani Eka; Nindrea, Ricvan Dana; Utami, Widy Nur; Rezvi, SM (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: A novel coronavirus-caused pneumonia has been widespread worldwide since the end of 2019. The rapid widespread has prompted the repurposing of drugs based on promising in vitro and therapeutic results with other human coronavirus diseases. These repurposed drugs have mainly included remdesivir, favipiravir, lopinavirritonavir, ribavirin, interferons, and hydroxychloroquine. AIM: This study aims to evaluate the efficacy of any antiviral for 2019-nCoV infection in a national referral hospital. METHODS: This research was a retrospective study to evaluate all antiviral clinical responses used in a national referral hospital. RESULTS: Based on gender, there is a similar frequency from all patients. Hematology, followed by cardiovascular and pulmonary disease, is the most frequent comorbidity. There is no significant difference between the two groups antiviral treatment for a length of stay parameter. The most extended length of stay is 29 days. About 64.5% of patients are cured of SARS-Cov-2 infection. In the remdesivir group, we find that the mortality is significantly high. CONCLUSION: The clinical outcome of these antiviral treatments is similar, except for mortality. The severity of COVID-19 causes differences in mortality.